Prevalence and distribution of soil-transmitted Helminthiasis among school-aged children in Kano, Northern Nigeria - Adamu, Rabiu; Abd. Aziz, Nor Azwady; Mustafa, Muskhazli; Shohaimi, Shamarina (Zagazig University, 2023)
Soil-transmitted Helminth (STH) are species of nematodes spread by eggs present in human faeces which contaminate the soil and cause an infection called helminthiasis. There are three STH; Roundworm (Ascaris lumbricoides), Hookworm (Ancylostoma duodenale and Necator americanus), and Whipworm (Trichuris trichiura). The study investigates the prevalence and distribution of STH infections among primary school children (PSC) in Dawakin Kudu local government, Kano State, Nigeria. Methods: Fecal samples (n=560) were collected from randomly selected pupils between the ages of 5 – 16 years from seven primary schools (PS), 80 pupils were enrolled in the study from each school. The samples were examined for the presence of STH eggs or larvae using the formol-ether sedimentation technique and analysed using IBM SPSS statistics version 26. Results: Out of 560 PSC examined for infections, 357(63.8%) were males while 203 (36.2%) were females. An overall prevalence was 338 (60.4%) positive with STH parasite and only 52(9.8%) had mixed infections. The prevalence of STH was Hookworm 197 (35.2%), Ascaris lumbricoides 109 (19.5%), and Trichuris trichiura 32 (5.7%). Gender specific rate for females 181 (32.3%) was higher than for males 157 (28.1%). The highest prevalence in both males 91 (16.3%) and females 106 (18.8%) was recorded in Hookworm infection and the least gender-specific infection was recorded in Trichuris trichiura infection with males 17 (3.0%) and females 15 (2.7%). However, there was no statistically significant difference in the prevalence of infection between gender (p=0.684) (p>0.05; 95% CL). The prevalence of parasites by age showed that the highest (18.9%) was recorded in children 8 – 10 years of age and the least prevalence (7.9%) was recorded between the 14 – 16 years age group. Across all four (4) age groups (5-7, 8-10, 11-13, 14 16 years), Hookworm had the highest prevalence (35.2%) and Trichuris trichiura infection was the least (5.7%) recorded prevalence. Conclusion: Programs such as public health enlightenment, regular de-worming exercises, supply of potable drinking water and personal hygiene should be intensified in the area particularly among children of school age.